Production method for epoxy resin composition, liquid discharge head using the epoxy resin composition, and manufacturing method for the liquid discharge head
Patent Information
- Application Number
- JP2024206617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-01-17
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-10-30
AI Technical Summary
【0008】 1液で十分な可使時間があり、短時間での加熱硬化性に優れ、接着信頼性の高い接着剤 として有用なエポキシ樹脂組成物が得られる。
Smart Images

Figure 2025024241000007 
Figure 2025024241000008 
Figure 2025024241000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an epoxy resin composition, and a method for discharging liquid using the epoxy resin composition. The present invention relates to a liquid ejection head and a method for manufacturing the same. [Background technology]
[0002] Epoxy adhesives are widely used due to their high adhesiveness and chemical resistance. For joining precision parts, it is important to have a quick hardening time (also called temporary fixing) to prevent misalignment. ) is required. A representative example of an epoxy adhesive with such properties is a photocationic polymerization type epoxy. Resin adhesives are one example. These adhesives are one-part adhesives with a long pot life and can be hardened by heating for a few seconds. For example, the change in physical properties such as viscosity at room temperature is small, This allows the adhesive to be applied stably to the adherend. In addition, after application, UV irradiation is performed to laminate the adherends. It hardens at 00°C for a few seconds, so it is difficult for the adhesive to shift out of position and there is no need to hold the adherend in place for long periods. If necessary, additional heating can be performed to further increase the crosslink density. In this way, the two-stage curing process improves productivity and chemical resistance. It improves reliability.
[0003] Photo-induced cationic polymerization epoxy resins form ether bonds by opening the epoxy ring. However, since ether bonds are formed, the hydroxyl groups, etc. The functional groups that contribute to adhesion may decrease, resulting in insufficient adhesion. The epoxy resin polymerization reaction has a fast reaction rate, and polythiol is used as a hardener. Polythiol is cured in the presence of a basic catalyst or a curing accelerator. This is an anionic polymerization that reacts rapidly with epoxy resin in the presence of thiol. As an adhesive, the adhesive described in Patent Document 1 is known. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 171072 Summary of the Invention [Problem to be solved by the invention]
[0005] Thiol curing is extremely reactive, but it can be difficult to apply it to multiple substrates using a syringe. The usable life is short, and some kind of ingenuity is required for practical use. In such thiol curing, a solid basic catalyst is used as a means of extending the pot life. For example, a solid basic compound can be used for thiol curing. The use of , it takes more time for it to dissolve and become a basic catalyst. The epoxy resin used, as well as the polythiol hardener, are usually liquids. Lithionol is easy to dissolve solid basic compounds, and can slightly delay the start of the reaction. Even if the amount of the basic compound is increased, the pot life may still be insufficient. Even if we succeed in extending the pot life by reducing the amount of heat, the hardening properties of the resin when heated for a short period of time will be poor. In some cases, the temporary adhesion is not sufficient. To solve the pot life problem, the adhesive is not used as a single component. If two liquids are used instead of one liquid, it is necessary to mix them, fill them into a syringe, and set them in the device each time. In addition, the reaction continues after mixing, so the pot life is short, which further reduces productivity. Inferior to.
[0006] The object of the present invention is to develop an epoxy resin which has a sufficient pot life and can be cured by heating for a short time. The present invention also provides an epoxy resin composition. A liquid ejection head and a method for manufacturing the liquid ejection head are provided. [Means for solving the problem]
[0007] The present invention, which achieves the above object, Method for producing epoxy resin composition containing epoxy resin, solid basic compound, and polythiol The method comprises the steps of kneading the epoxy resin and the solid basic compound to produce a mixture 1; and kneading the mixture 1 with a polythiol to produce a mixture 2. The present invention relates to a method for producing an epoxy resin composition comprising the steps of: The present invention also relates to a composition comprising an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol. A method for producing an epoxy resin composition comprising kneading the epoxy resin and the thixotropic agent. a step of producing a mixture 3, and a step of kneading the solid basic compound with the mixture 3 to produce a mixture 4. and kneading the mixture 4 with the polythiol to produce a mixture 5. The present invention relates to a method for producing an epoxy resin composition, Furthermore, the present invention relates to a method for producing a polymerizable composition comprising an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol. A method for producing an epoxy resin composition comprising the steps of: mixing the epoxy resin with the solid basic compound; a step of kneading the polythiol and the thixotropic agent to produce a mixture 6; and kneading the mixtures 1 and 6 to produce a mixture 7. The present invention relates to a method for producing an epoxy resin composition comprising the steps of: Alternatively, an epoxy resin containing an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol A method for producing an epoxy resin composition, comprising kneading the epoxy resin and the thixotropic agent to form a mixture (3), a step of kneading the solid basic compound with the mixture 3 to produce a mixture 4; A step of kneading the polythiol and the thixotropic agent to produce a mixture 6; and kneading the mixture to produce a mixture 8. It concerns the method. By using any of the above-mentioned manufacturing methods, at least an epoxy resin, a solid basic compound, and and polythiol, and the epoxy resin is 100 parts by mass of the solid base. Although the content of the reactive compound is 3 to 10 parts by mass, a one-liquid epoxy resin composition can be obtained. . In addition, the present invention includes a recording element substrate that ejects ink, a recording device that supports the recording element substrate, and A support member having a supply flow path for supplying ink to a recording element substrate, and an ink supply passage for supplying ink to the supply flow path. A method for manufacturing a liquid ejection head having a flow path member for supplying epoxy resin to said method. A step of producing an adhesive by a method for producing a resin composition, and and applying the adhesive to at least one joint surface between any two of the flow path members. and then bonding the two members together. Effect of the Invention
[0008] A one-part adhesive with sufficient pot life, excellent heat curing in a short time, and highly reliable adhesion. Thus, an epoxy resin composition useful as an epoxy resin composition for use in ... is obtained. [Brief description of the drawings]
[0009] [Figure 1]FIG. [Diagram 2] FIG. 1 is a schematic cross-sectional view of an inkjet head. [Diagram 3] FIG. 1 is a schematic diagram showing a state when adhesive strength is measured by the butting method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention relates to an epoxy resin comprising an epoxy resin, a solid basic compound, and a polythiol. A composition (adhesive) is provided. However, solid basic compounds tend to dissolve in polythiols with a relatively low viscosity. Sometimes, a solid basic compound is coordinated to the polythiol, and the epoxy resin and the polythiol are reacted very quickly. Therefore, it is possible to use such a solid basic compound as a catalyst. It seemed like there wasn't enough time.
[0011] However, according to the investigations of the present inventors, it has been found that the surface of a solid basic compound can be covered with an epoxy resin. It has been found that the dissolution of a solid basic compound in a polythiol having a relatively low viscosity can be suppressed by using the above-mentioned method. The solid basic compound wrapped in epoxy resin was dissolved in polythiol and became a basic catalyst. It takes time for the epoxy resin and polythiol to start reacting. Even at room temperature, the viscosity of the liquid increases slowly, providing sufficient usable time. By wrapping the surface of the compound in epoxy resin, sufficient pot life is ensured, This allows the addition of solid basic compounds in amounts that would have been impossible otherwise, increasing the number of reaction initiation points. Furthermore, it can be cured by heating for a short period of time. In particular, in systems where a thixotropic agent is added, the thixotropy is expressed, It can be applied and adhered without spreading, making it excellent for application to small areas. The viscosity of the epoxy resin and / or polythiol is increased by the agent, and the solid basic compound is Dissolution in lithiol can be further suppressed, resulting in a longer pot life.
[0012] The adhesive obtained by the method of the present invention is a basic thiol-curing adhesive, so the curing reaction This makes it difficult for functional groups that contribute to adhesion, such as hydroxyl groups, to be reduced, resulting in excellent adhesion. For this reason, the method for producing an adhesive according to one embodiment of the present invention comprises the steps of: A process is carried out by kneading the compound to prepare a mixture 1 and kneading the polythiol into the mixture 1. This process results in the solid basic compound being covered with epoxy resin. Therefore, it is possible to suppress the dissolution contact of solid basic compounds with polythiol, and it is possible to Even at room temperature, the viscosity rises slowly, and the adhesive of the present invention has a sufficient pot life.
[0013] In another embodiment of the method for producing an adhesive of the present invention, the adhesive may be produced by using an epoxy resin and / or a polyamide resin. By going through the process of kneading the thixotropic agent into the thiol in advance, the solid basic compound is added to the polythiol. This allows the dissolution contact of the material to be suppressed. As a result, the usable time of the single liquid can be guaranteed. This thixotropic agent allows the solid basic compound to be mixed in a larger amount, and the ethylenediaminetetraacetate, which is inherently highly reactive, can be used in the same manner. It can further improve the thiol curing property of epoxy. It can be cured in a few seconds at a temperature of about 100°C, and has excellent temporary adhesion. Thus, an adhesive having a satisfactory pot life can be obtained.
[0014] The adhesive of the present invention is a thiol curing (anionic polymerization reaction) adhesive, and even after curing, it does not retain adhesion groups such as hydroxyl groups. The functional groups that contribute to the synthesis remain, and the thiol-derived -S- is flexible and can withstand harsh environments. For example, inkjet heads are used in liquid-based printers. It can be used as an adhesive to bond the parts of the inkjet head. The ink used is made of a polar solvent, water, and coloring material, and the area that comes into contact with the ink is pasted. The adhesive must maintain a strong adhesive force. In addition, the color of the liquid must be different between the separated liquid channels. In order to prevent the adhesive from mixing, it is desirable to maintain a strong adhesive force at the interface between the adherend and the adhesive. If a gap occurs at the interface between the body and the adhesive, ink will enter the gap through the liquid flow path of each color due to capillary force. This is because there is a higher probability of different colors mixing together.
[0015] In addition, during the inkjet head manufacturing process, small parts are fixed with adhesive so that they do not move. Then, the next part is attached, and the process is repeated. Finally, a relatively long time is spent The process of fixing the parts with adhesive so that they do not move is called temporary fixing. The process of hardening the adhesive over a relatively long period of time is called the main hardening stage. For example, 100 The adhesive is temporarily fixed at 100°C for a few seconds, and then fully cured at 150°C for two hours. It cures in just a few seconds at a temperature of about 100°C, making it suitable for the temporary fixing process of inkjet heads. .
[0016] Each component will be described below. (Epoxy resin) The epoxy resin as the main component may be one type or may contain two or more types. Since it is necessary to cover the solid basic compound as a catalyst, a process of kneading the solid basic compound is required. In this process, the epoxy resin composition must be liquid. In this case, heat the solid basic compound to a temperature at which it will not melt, or use another liquid epoxy compound. It is recommended to dissolve it in resin.
[0017] Epoxy resins include bisphenol A, bisphenol F, and bisphenol A. D-type epoxy resins and compounds in which alkylene oxide is added to these. Diglycidyl ether, epoxy novolac resin, bisphenol A novolac diglycidyl ether glycidyl ether type such as bisphenol F novolak diglycidyl ether, Glycidylamine epoxy resins and alicyclic epoxy resins are examples. Epoxy resins include those with a biphenyl skeleton, a naphthalene skeleton, a cresol novolac skeleton, Trisphenolmethane skeleton, dicyclopentadiene skeleton, phenolbiphenylene skeleton and the like.
[0018] (Polythiol) The polythiol used as the curing agent is not particularly limited, but is usually one that is highly reactive and relatively Select a polythiol with a low molecular weight. Such a polythiol should be liquid at room temperature. Mostly. For example, pentaerythritol trispropanethiol (PEPT), trimethylol Tris(3-mercaptopropionate) (TMMP), Pentaerythritol tetrakis(3-mercaptopropionate), p-xylene dithiol, etc. Some examples include: Commercially available products include PEPT (manufactured by SC Organic Chemicals), TMMP (manufactured by SC Organic Chemicals), Upcure 3-800 (product name, manufactured by Mitsubishi Chemical Corporation), QX11 (product name, manufactured by Mitsubishi Chemical Corporation) (manufactured by the company) When the adhesive of the present invention is used in a portion where more chemical resistance is required, the more chemically resistant ether is used. A polythiol having an ether skeleton is preferably a polythiol having a side chain It has two or more thiol groups, does not contain hydrolyzable ester bonds in the main chain, and has a strong bond strength This refers to a compound having an ether bond that has excellent properties such as chemical resistance due to its high molecular weight.
[0019] The content of polythiol is the ratio of the thiol of polythiol to 1 epoxy equivalent of epoxy resin. The amount of the polyether compound is preferably 0.5 to 1 equivalent. As the amount of thiol decreases, the reaction rate between the epoxy resin and polythiol decreases. The reaction rate of the entire system may slow down, and curing in a short time may not be achieved. If the equivalent weight of the ol is low, the polymerization reaction between the epoxy resin and the polythiol is not the main reaction, The main reaction may be a polymerization reaction between the epoxy resin and the base derived from the solid basic compound. Therefore, the flexibility of the thioether structure (-S-) derived from polythiol is reduced. From the viewpoint of adhesion, this is not preferable. The equivalent weight of polythiol becomes too high relative to the epoxy resin. If the temperature is too high, the amount of polythiol that cannot react with the epoxy resin will increase. The thiol remains as a plasticizer, and may deteriorate the mechanical properties, such as reducing adhesive strength. In addition, if adhesive is used in areas that come into contact with ink, unreacted polythiol will leach into the ink. Ink fills the space left by the dissolved polythiol, causing the adhesive to swell with the ink. This is not desirable because it may cause
[0020] (Solid basic compounds) The solid basic compound serving as the curing catalyst is not particularly limited as long as it is solid at room temperature. In particular, epoxy resins that are difficult to dissolve are preferably used. For example, dicyandiamide and dihydrazide, which are commonly used as latent hardeners, The compounds diaminodiphenylmethane (DDM) and diaminodiphenylsulfone (DDS) ) and other solid aromatic amines, various imidazoles, and various amine adduct-based latent hardeners. Some examples include:
[0021] The content of the solid basic compound is 3 to 10 parts by mass per 100 parts by mass of the epoxy resin. If the amount of the solid basic compound relative to the epoxy resin becomes too small, If the amount of solid basic compound is too large relative to the epoxy resin, Although the solid basic compound is protected by epoxy resin, it dissolves in polythiol. In particular, the amount of the basic compound increases, and the pot life is shortened. While maintaining sufficient pot life, the solid basic compound is It becomes possible to add a large amount, such as 3 to 10 parts by mass.
[0022] (thixotropic agent) It reduces the fluidity of the liquid component and further suppresses the dissolution of the solid basic compound in the polythiol. For the purpose of this, the components other than the above epoxy resin, solid basic compound, and polythiol are Therefore, a thixotropic agent may be added to the epoxy resin composition (adhesive).
[0023] As a thixotropic agent, inorganic fine particles such as general fumed silica are used. There are also liquid types that can impart thixotropy without increasing the viscosity too much, but in this case In this case, glass, titanium oxide, alumina, aluminum hydroxide, magnesium hydroxide, talc Other fillers such as silane, mica, and silica are required. Use of esters, hydrogenated castor oil, polyethylene oxide, surfactants, etc. These may be used alone or in combination of two or more.
[0024] The content of the thixotropic agent is preferably 1 to 20 parts by mass relative to 100 parts by mass of the epoxy resin. The more thixotropic agent there is, the longer the pot life tends to be. The amount of the thixotropic agent should be adjusted accordingly. The method of mixing the thixotropic agent will be described later.
[0025] (Method of producing epoxy resin composition) In the method for producing the epoxy resin composition (adhesive) according to the present invention, a solid salt is added to the polythiol. In order to prevent dissolution of the radical compounds, the raw materials for the adhesive are mixed in the following order:
[0026] (Adhesive that does not contain thixotropic agents) In the method for producing an adhesive according to the present embodiment, an epoxy resin and a solid basic compound are mixed and kneaded. A step of producing a mixture 1, and a step of kneading the mixture 1 with a polythiol to produce a mixture 2. The epoxy resin, the solid basic compound, and the epoxy resin may be mixed in the same order. Compared to mixing all the lithiol at once, the adhesive mixed in the above order Even when stored at room temperature, the viscosity did not increase much and the pot life was sufficient. The adhesive has a sufficient pot life, so the amount of adhesive mixed at once is not possible. It is possible to add a solid basic compound, and it is expected that the curing will take place in a short time.
[0027] (Adhesives containing thixotropic agents) Furthermore, the production of an adhesive containing a thixotropic agent can be carried out in the following order of steps. First, a step of kneading an epoxy resin and a thixotropic agent to produce a mixture 3; a step of kneading the mixture 3 with a solid basic compound to produce a mixture 4; A step of kneading the mixture 4 with a polythiol to produce a mixture 5. The adhesive mixed in this order had a longer pot life. Alternatively, a mixture 1 is prepared by kneading an epoxy resin and a solid basic compound. a step of kneading the polythiol and the thixotropic agent to produce a mixture 6; The method may further include a step of kneading mixture 6 to produce mixture 7. In this case, The viscosity of the thiol increases due to the thixotropic agent, and the solid basic compound is coated with epoxy resin. The contact with the polythiol is further suppressed. Alternatively, the above mixture 4 is prepared, and the mixture 4 is and the mixture 6 to produce the mixture 8. In this case, Thixotropic agents can be mixed in, further extending the pot life.
[0028] (Silane coupling agent) A silane coupling agent may further be added to the adhesive of the present invention. Silane coupling agents include those with epoxy groups, mercapto groups, isocyanate groups, and fluoro groups. A silane coupling agent having an olefin skeleton can be used. The coupling agent is a low-viscosity liquid, so it can be used with basic silane coupling agents such as amine compounds. The agent acts as a catalyst, immediately starts the reaction, and shortens the pot life. is not appropriate.
[0029] When the adhesive of the present invention is used in a situation where stronger adhesion is required at the interface between the adherend and the adhesive As the silane coupling agent, those having an epoxy group or a mercapto group are preferred. The base resin is epoxy resin and the hardener is polythiol, so these silanes It has good compatibility with coupling agents, and peeling at the interface between the adherend and the adhesive is unlikely to occur. It seems likely. The order of mixing the silane coupling agents is not particularly limited. The base compound is epoxy resin, and the mercapto group-containing silane coupling agent is polythio It is preferable to mix them at the same time as the injection.
[0030] (Other Ingredients) The resin composition containing the above components does not contain diluents or other agents commonly used in epoxy adhesives. Additives such as fillers may be added as needed. It can be implemented.
[0031] (Inkjet head) The epoxy resin composition of the present invention is used as an adhesive for bonding parts of an inkjet head. It can be suitably used as such. FIG. 1 is a perspective view showing one embodiment of an inkjet head, and FIG. The inkjet head 1 is a recording element that ejects ink. The substrate 2 supports the recording element substrate 2 and has a supply flow path 3 for supplying ink to the recording element substrate. The ink supply passage includes a support member for supporting the ink supply passage, and a flow passage member for supplying ink to the supply flow passage. The flow path member 5 may be composed of a plurality of parts. For example, as shown in FIG. The flow path member 5 may be composed of a first flow path member 6, a second flow path member 7, and a third flow path member 8.
[0032] In the manufacturing process of inkjet heads, two components, such as flow path components, are bonded together with high precision. Therefore, the assembly may be performed in the following order: The ink is applied to the third flow path member 8, and the ink is temporarily fixed to the recording element substrate in a short time. Then, the ink is completely cured. and the second flow path member 7 are bonded together, and the first flow path member 6 is further bonded to the second flow path member 7. Then, the support member 4 and the first flow path member 6 of the flow path member 5 are temporarily fixed together. Finally, the resin is allowed to fully harden.
[0033] The epoxy resin composition of the present invention has a sufficient pot life after being prepared as a one-part component, and Since it also has excellent temporary fixing properties, it is particularly useful as an adhesive for the joining surface between the support member 4 and the first flow path member 6. The joining surface between the first flow path member 6 and the second flow path member 7, the joining surface between the second flow path member 7 and the third flow path member 8, and the joining surface between the first flow path member 6 and the second flow path member 7 are preferably used. It can be suitably used for at least one joining surface between two members, such as the joining surface with the flow path member 8. Of course, it can also be suitably used for the bonding surface between the support member 4 and the recording element substrate 2. The support member 4 and the flow path member 5 are made of ceramics such as alumina or modified polyphenylene ether. Resins with excellent dimensional accuracy such as ether resins (Zylon (registered trademark), manufactured by Asahi Kasei Corporation, etc.) The adhesive of the present invention is a basic thiol curing adhesive. Therefore, functional groups that contribute to adhesion, such as hydroxyl groups, are relatively not lost during the curing reaction, and the ink-jet It can be suitably used as an adhesive for bonding parts of a printer head. EXAMPLES
[0034] Next, the method for producing the adhesive of the present invention will be described with reference to examples. (Examples 1 to 13, Comparative Examples 1 to 9) Table 1 shows the composition ratios of the examples, and Table 2 shows the composition ratios of the comparative examples. The mixing method is shown with arrows indicating the mixing order of each mixture. Mixture 1 (base material + curing catalyst), Mixture 2 (base material + curing agent), Mixture 3 (base material + gypsum) agent), Mixture 4 (Mixture 3 + curing catalyst), Mixture 5 (Mixture 4 + curing agent), Mixture 6 ( Hardener + Thixotropic Agent), Mixture 7 (Mixture 1 + Mixture 6), Mixture 8 (Mixture 4 + Mixture 6) ).
[0035] In Examples 1, 2, and 7, the epoxy resin as the base material and the solid basic compound as the catalyst were mixed together. After 12 hours, polythiol, which is a curing agent, was kneaded (mixture 1→2). In Examples 3 to 6 and 8 to 12, the epoxy resin as the base material and the thixotropic agent were mixed together, and then the catalyst After 12 hours, the hardener polythiol was added. mixture 3→4→5). In Example 13, the epoxy resin as the base material and the solid basic compound as the catalyst were mixed together to form a mixture. 1, and then knead and mix the polythiol hardener and silica filler thixotropic agent separately. After 12 hours, mixture 1 and mixture 6 were kneaded (mixture 1→6→7). In order to mix the thixotropic agent into the epoxy resin, which is the main component, a solid base catalyst is used. In Example 14, the epoxy resin, which is the main component, is used. Mixture 3 was prepared by kneading 10 parts by mass of silica filler, which is a thixotropic agent, with 100 parts by mass of the mixture. After the preparation, a solid basic compound serving as a catalyst was kneaded to prepare mixture 4. 66 parts by mass of polythiol as a thixotropic agent and 6.6 parts by mass of silica filler as a thixotropic agent Mixture 6 was prepared by kneading. After 12 hours, Mixture 4 and Mixture 6 were kneaded to prepare Mixture 8. (Mixture 3 → 4 → 6 → 8). In contrast, in Comparative Examples 1 to 9, all of the materials were kneaded simultaneously.
[0036] The epoxy resin, which is the main component, and the thixotropic agent are mixed using HIVIS MI manufactured by Primix. In X model 3, 60 rpm for 60 minutes in vacuum, epoxy resin and thixotropic agent were not included. The kneading was carried out in a vacuum at 60 rpm for 5 minutes.
[0037] The time it took for the viscosity to double at room temperature (25°C) was measured and used as the working life of the adhesive. The gel time was measured when heated at ℃, and the adhesive's quick hardening (temporary adhesion) was evaluated. Ta.
[0038] The judgment was as follows: ◎: Pot life is 8 hours or more and gel time is 3 seconds or less. 〇: Pot life is 3 hours or more and less than 8 hours, and gel time is more than 3 seconds and less than 10 seconds. ×: Pot life is less than 3 hours or gel time is 10 seconds or more.
[0039] In Comparative Examples 1 and 2, a liquid basic compound was used as a catalyst. In Comparative Example 1, the amount of catalyst was small. The gel time is long because the amount of catalyst added is large, as in Comparative Example 2, and the pot life is short. The gel time is not shortened. Epoxy resin, liquid basic compound, and polythio When the polythiol is mixed with the liquid basic compound, the pot life is increased. It seems that it is not possible to achieve both temporary fastening properties.
[0040] In Comparative Examples 7 to 9, a solid basic compound was used. In Comparative Example 1 and Comparative Example 9, the viscosity was doubled. The time to gel is the same as that of the comparative example 9, but the gel time is shorter in the comparative example 9. When a solid basic compound was used instead of a solid compound, it became somewhat closer to achieving both pot life and temporary fixing properties. However, the gel time of Comparative Example 9 was 78 seconds, which was long for a temporary fixing process. It lasts a long time, but it cannot be considered a temporary adhesive. In order to improve the temporary fixing property of Comparative Example 9, the amount of the solid basic compound was increased in Comparative Examples 6 to 8. The more the amount of the solid basic compound was, the shorter the gel time became and the better the temporary fixing property became. The pot life was shortened. The product is made of epoxy resin, polythiol, and solid base compound. When all the materials are mixed at the same time, the epoxy resin is required to obtain sufficient pot life. The solid basic compound is less than 3 parts by mass, or even 0.5 parts by mass or less, per 100 parts by mass of fat. When the amount of the solid basic compound is less than 3 parts by mass, sufficient pot life is obtained. However, it cannot be said to be a temporary adhesive.
[0041] In Example 1 and Comparative Example 3, and in Example 2 and Comparative Example 6, the same composition was used, but the manufacturing method was changed. As can be seen from the comparison between Example 1 and Comparative Example 3, and between Example 2 and Comparative Example 6, the gel time is the same. However, in the examples of the present invention, the working life is significantly extended. Since the solid basic compound is covered with an epoxy resin, it is possible to suppress the dissolution of the solid basic compound into the polythiol. This is thought to have resulted in a slow increase in viscosity even at room temperature with one liquid, and therefore a longer pot life. On the other hand, since the composition is the same, the gel time did not change. The solid basic compound, which is the catalyst, is kneaded to form a mixture, and the mixture is added with polythiol, which is the hardener. By going through a process of kneading the above, an adhesive was created that had both long pot life and good temporary bonding properties.
[0042] The amount of the solid basic compound added as the catalyst was as shown in Comparative Examples 6 to 9. In terms of the composition of the ester-type hardener, which has a relatively slow reactivity, if it is 3 parts by mass or more, the gel time is 1 The gel time is shorter as the amount of solid basic compound added increases. If the amount is more than 10 parts by mass, the viscosity of the adhesive itself will increase and the amount of unreacted catalyst will also increase. However, in Comparative Examples 6 to 9, the solid basic compound is not added in advance. Since it does not go through a process of covering with epoxy resin, its pot life is short.
[0043] In Examples 3 to 5, the influence of the type of solid basic compound used as the catalyst was examined. Even with the use of a basic compound, both pot life and temporary fixing properties were achieved. In Examples 5 and 6, the effect of the type of polythiol used as the curing agent was examined. The thiol also achieved both pot life and temporary fixing properties. In all cases, the temporary fixing time was shorter with the polythiol having an ether skeleton. When temporary adhesion is required, highly reactive ether-type polythiols are preferred.
[0044] In Examples 7 to 14, the amount of the thixotropic agent was examined. In comparison with no addition (0 parts by mass) in Example 7, up to 1 and 2.5 parts by mass in Examples 8 and 9 The addition of a thixotropic agent to the epoxy resin covers the solid basic compound, and the working time is extended. This increases the viscosity of the epoxy resin and improves its thixotropy. The solid basic compound acts as a basic catalyst to prevent dissolution of the solid basic compound into the eluate. This is thought to be because it took time for the polymerization reaction between the epoxy resin and the polythiol to begin. In Examples 10 to 12, even if the amount exceeds 2.5 parts by mass (up to 5, 10, and 15 parts by mass), the pot life There is almost no change. The effect of suppressing the dissolution of solid basic compounds into polythiol This is thought to be because the In Example 13, a polyol thixotropic agent was added. Compared to Example 7, which did not contain the agent, The time was extended slightly. The addition of a thixotropic agent to polythiol resulted in the solid basicity of the polyol. It appears that the dissolution of the compound was suppressed. The epoxy resin of Example 14 was mixed with 10 parts by mass of a thixotropic agent, and the polythiol was mixed with 6.6 parts by mass of a thixotropic agent. The total content of the thixotropic agent was 100 parts by mass of epoxy resin. By increasing the ratio to 6.6 parts by mass, the working life is further extended. By adding a thixotropic agent to both the solid base compound and the polythiol, the dissolution of the solid base compound in the polythiol can be promoted. It is believed that this further suppresses the effect of the thixotropic agent. Yes, but if you want a longer pot life, you may need to use a thixotropic agent, depending on the type of base resin and hardener. It is preferable to add the above-mentioned, and the content of the above-mentioned is preferably 1 to 20 parts by mass. It was acknowledged.
[0045] [Table 1]
[0046] [Table 2]
[0047] The abbreviations in the table are as follows. The same applies to the following tables. jER828: Product name, bisphenol A type epoxy resin (epoxy equivalent: 184-1 94) Mitsubishi Chemical Corporation jER152 product name, manufactured by Mitsubishi Chemical Corporation Aerosil 200: Product name "AEROSIL200", manufactured by Nippon Aerosil Co., Ltd. PEPT: Pentaerythritol tripropanethiol (thiol equivalent: approx. 115) , manufactured by SC Organic Chemical Co., Ltd. TMMP: Trimethylolpropane tris(3-mercaptopropionate)(thio equivalent weight: approx. 133), manufactured by SC Organic Chemicals PN23J: Product name "Amicure PN-23J", manufactured by Ajinomoto Fine-Techno Co., Ltd. MY-24: Product name "Amicure MY-24", manufactured by Ajinomoto Fine-Techno Co., Ltd. MY-25: Product name "Amicure MY-25", manufactured by Ajinomoto Fine-Techno Co., Ltd. PN40J: Product name "Amicure PN-40J", manufactured by Ajinomoto Fine-Techno Co., Ltd. 1B2PZ: Product name "Curesol 1B2PZ", manufactured by Shikoku Chemical Industry Co., Ltd.
[0048] (Examples 15 to 27) Tables 3 and 4 show the composition ratios of Examples 15 to 27. The composition ratios of Examples 5 and 6 are also shown. vinegar. In Examples 15, 17 to 19, mixture 3 was prepared in the same manner as in Example 14, and then silane was added to mixture 3. Add a coupling agent and knead, then add a solid basic compound as a catalyst and knead. Mixture 4 was prepared by mixing the remaining thixotropic agent with the polythiol curing agent. Mixture 6 was prepared. After 12 hours, mixture 4 and mixture 6 were kneaded to prepare mixture 8. In Example 16, a mercapto group-containing silane coupling agent is used, so silane coupling Mixture 8 was prepared in the same manner as in Example 14, except that the blocking agent was added to Mixture 6. In addition, in Examples 20, 21, and 23 to 27, mixture 3 was prepared in the same manner as in Example 11, and then the mixture was mixed. A silane coupling agent is added to the substance 3 and kneaded, and then a solid basic compound as a catalyst is added. After 12 hours, the mixture 4 was mixed with polythiol as a curing agent. In Example 22, the hardener polythiophene was added at the stage of preparing Mixture 5. A mercapto-based silane coupling agent was kneaded together with the silane.
[0049] The epoxy resin, which is the main component, and the thixotropic agent are mixed using HIVIS MI manufactured by Primix. In X model 3, 60 rpm for 60 minutes in vacuum, epoxy resin and thixotropic agent were not included. The kneading was carried out in a vacuum at 60 rpm for 5 minutes.
[0050] The adhesive was evaluated by the following methods. The evaluation of the adhesive's pot life and gel time, and whether they were compatible, was carried out in the same manner as above. Ta. In addition, 2 g of the cured product that had been heated at 160°C for 2 hours was used as ink (service head ink cartridge). The test piece was immersed in 20 g of acrylic resin (Non- ... The mass change rate was calculated by comparing with the mass before immersion. Furthermore, the components that make up the inkjet head (alumina and alumina) are bonded together with adhesive. The adhesive 2 was applied to the base 24 as shown in FIG. The alumina plates 21 and 22 bonded together in step 3 are placed on top of each other, and measurements are taken through a hole made in the alumina plate 21. The adhesive strength was measured by a method in which a jig was pressed against the surface. The state of peeling was also observed. In the case of part destruction, the peel strength cannot be measured accurately, so the peel strength is displayed as ND. In addition, the parts were bonded together with adhesive, heated at 160°C for 2 hours, and then immersed in the above ink. After washing with water and drying, the adhesive strength was measured using the impact method. At the same time, the state of peeling was observed.
[0051] How to determine which adhesive is suitable for inkjet heads ◎: Adhesive strength 1.0kgf / mm 2 (9.8N / mm 2 ) does not peel off, but if you press it further and ends with component destruction. 〇: Adhesive strength is 1.0kgf / mm 2 (9.8N / mm 2 ) and interface peeling was confirmed. .
[0052] As described above, in Example 5, a polythiol having an ester skeleton (TMMP) was used, and in Example In 6, a polythiol having an ether skeleton (PETE) was used. PETE and TMMP are Since the molecular weights of the thiol groups were different, different parts by weight of each polythiol were mixed. The mass change rate of PETE, which has an ether structure, was higher than that of TMMP, which has an ester structure. The adhesion strength after contact with ink was strong. Compared to the ester structure, the ether structure This is thought to be because of its high chemical resistance, high reactivity, and high crosslink density. Compared with polythiols that use ether structures, polythiols with ether structures are more suitable for inkjet printing. It is suitable as an adhesive for bonding components of a metal frame.
[0053] In Examples 15 to 22, the effect of the type of silane coupling agent was examined. Even with the use of a coupling agent, both the pot life and temporary adhesion were achieved, and sufficient adhesive strength was also achieved. Among them, those containing epoxy groups or mercapto groups as silane coupling agents are When using this adhesive, the adhesive strength was measured after contact with the ink, and it was found that the part was broken rather than the interface peeling. When bonding inkjet head parts together, different colors do not mix. For this reason, adhesives that destroy components are preferable to adhesives that cause interface peeling. Epoxy or mercapto group-containing silane caps are used as adhesives to bond the parts of the head. Adhesives with added pulling agents are more preferable. The adhesive contains epoxy resin as the main agent, Contains polythiol as a curing agent, so epoxy or mercapto group-containing silanes It is believed that the coupling agent had good compatibility with the base agent and hardener, and therefore no interfacial peeling occurred.
[0054] In Examples 20 and 23 to 25, the amount of polythiol added was examined. Even with the amount of polythiol, both pot life and temporary fixation were achieved. In order to maintain the temporary adhesion, the epoxy resin should be 100% epoxy equivalent. The thiol equivalent of the polythiol is preferably 0.5 or more. The mass change rate increased as the amount of polythiophene increased. The amount of polythiol that could not react was increased, and the polythiol was dissolved into the ink, and the voids where the polythiol had disappeared were formed. It is believed that the ink penetrated between the two, causing a large change in mass. In order not to increase the amount of thiol in polythiol, the epoxy equivalent of epoxy resin should be The equivalent weight is preferably 1 or less.
[0055] In Examples 20, 26, and 27, the mixing ratio of two types of epoxy resins was varied. In addition, the adhesive used for bonding inkjet head parts was also tested. It was also suitable for use as a bonding adhesive.
[0056] [Table 3]
[0057] [Table 4]
[0058] The silane coupling agents in the table are as follows. A-186: Product name "Silquest A-186", Momentive Performance Material Group Made by Pan A-187: Product name "Silquest A-187", Momentive Performance Material Group Made by Pan KBM-803: Product name, 3-mercaptopropyltrimethoxysilane, Shin-Etsu Chemical Co., Ltd. Company KBE-9007: Product name, 3-isocyanatepropyltriethoxysilane, Shin-Etsu Chemical Manufactured by Gaku Kogyosha X-12-1156: Product name, multifunctional mercapto group type silane coupling agent, Shin-Etsu Chemical Made by Kogyosha X-12-1159L: Product name, multifunctional isocyanate-based silane coupling agent, Manufactured by Etsu Chemical Industry Co., Ltd. OCG-157-3: Fluorene-based silane coupling agent, manufactured by Osaka Gas Chemicals Co., Ltd.
[0059] (Example 28) Generally, when the adhesive is a mixture of liquid and solid components, the adhesive If used in narrow spaces with a diameter of several tens of micrometers, the movement of the solid components will be restricted by the narrow gap, causing the mixture to separate. This causes bleeding during the curing reaction, resulting in poor curing. Since there was concern about bleeding, the presence or absence of bleeding was confirmed by the following procedure. In the examples, the substrates were laminated using spacers of a specified size. The thickness was varied to 10, 20, and 30 μm, and the presence or absence of bleeding and hardening was checked. In both cases, no bleeding was observed, and no uncured components were identified. This is because the solid components were in contact with the This is because the reaction proceeds with only a small amount of catalyst, whereas the method of the present invention uses a large amount of catalyst. It is believed that this is due to the fact that the curing agent is a polythiol, which is highly reactive.
[0060] The adhesive of the present invention has a first heat curing step, which is a temporary fixing step, and a second heat curing step, which is a temporary fixing step. By performing the second heat curing, which is the longest main curing time, in two steps, it is possible to achieve high-precision lamination. It is suitable for joining etc. For example, a silicon substrate on which ink ejection pressure generating elements and wiring for applying electric pulses are formed. The ink supply is made of alumina to the recording element on which the ink flow path and the ejection port are provided. In such cases, the flow paths must be bonded together with high precision. In order to achieve this, it is necessary to maintain the alignment and allow the adhesive to harden. It takes at least one hour for the material to harden and then it is heated and hardened after being aligned with a jig or similar. It is extremely difficult to hold the material in place in a heat tool. is directly applied to the Si substrate of the recording element and heated; if the temperature is 100°C, it hardens in a few seconds and is temporarily fixed. It is possible. After the temporary fixing, the adhesive will harden, so even if the jig is removed, the parts will not move. The final curing can be done in a decomposition oven. The second heat curing, which is the final curing, is done to fully harden the adhesive. The second heat curing takes longer than the first heat curing, which is a temporary fixation. The curing time and temperature are preferably higher than the first heat cure. The optimum ratio of the base resin, hardener, solid basic compound, and other additives is selected. In particular, if a thixotropic agent is added to the system, it is possible to use the inkjet head. The flow of adhesive into the fine flow paths of the head can also be controlled, and by using ether-type polythiol, This will ensure high ink resistance and adhesive reliability.
[0061] As shown in Table 5, in Example 21, the solid basic compound PN40J was added in an amount of 5 to 3 parts by mass. An adhesive was prepared in the same manner, except that the amount was changed to parts by mass. Two modified polyphenylene ether resin plates (product name "Zylon ( A PPE film (registered trademark: L564Z, manufactured by Asahi Kasei Corporation, abbreviated as m-PPE) was attached to the substrate. Allowed to cure for 2 hours. When the parts were peeled off using the butting method, the adhesive failed cohesively. It had sufficient adhesion to the m-PPE resin plate.
[0062] [Table 5]
[0063] (Examples 29 to 37) In Examples 29 to 37, thick coating properties were examined. If the adhesive is too thin, it may not spread sufficiently and may peel off during use. Therefore, we investigated whether the adhesive could be applied thickly. Table 6 shows the composition ratios of Examples 29 to 37. The composition ratio of Example 16 is also shown. Example 29 was prepared in the same manner as Example 16, except for the addition of the filler fused silica. In the same manner as in Example 14, thixotropy was used for 100 parts by mass of the epoxy resin, which is the main component. Mixture 3 was prepared by kneading 10 parts by mass of silica filler, which is a catalyst, and an organic thixotropic agent. A solid basic compound was kneaded to prepare mixture 4. A mixture of 66 parts by mass of thiol and 6.6 parts by mass of silica filler, which is a thixotropic agent, was kneaded. After 12 hours, mixture 4 and mixture 6 were mixed to prepare mixture 8 (organic Thixotropic agent mixture is mixture 3).
[0064] In Example 36, silica, a thixotropic agent, was added to 100 parts by mass of the epoxy resin, which is the main component. Mixture 3 was prepared by kneading 10 parts by mass of filler, and then a solid basic compound serving as a catalyst was kneaded therein. Mixture 4 was prepared by mixing 66 parts by mass of polythiol, which was a curing agent, with thiol. Mixture 6 was prepared by kneading 6.6 parts by mass of silica filler, which is a thixotropic agent, and an organic thixotropic agent. After 12 hours, mixture 4 and mixture 6 were kneaded to obtain mixture 8 (organic thixotropic agent mixture). In this case, a mixture6).
[0065] In Example 37, silica, a thixotropic agent, was added to 100 parts by mass of the epoxy resin, which is the base material. Mixture 3 was prepared by kneading 10 parts by mass of filler and 1.5 parts by mass of organic thixotropic agent, and then the mixture was mixed with a catalyst. Mixture 4 was prepared by kneading a certain solid basic compound. 6.6 parts by mass of silica filler (thixotropic agent) and 6.6 parts by mass of organic thixotropic agent for 66 parts by mass of all. Mixture 6 was prepared by kneading 1.5 parts by mass of the agent. After 12 hours, Mixture 4 and Mixture 6 were mixed. The mixture was kneaded to obtain mixture 8. (The organic thixotropic agent mixtures were mixtures 3 and 6).
[0066] The epoxy resin, which is the main component, and the thixotropic agent are mixed using HIVIS MI manufactured by Primix. In X model 3, 60 rpm for 60 minutes in vacuum, epoxy resin and thixotropic agent were not included. The kneading was carried out in a vacuum at 60 rpm for 5 minutes. The thickness of the adhesive was evaluated by the following method. The thixotropy was measured using a viscometer. Specifically, the viscometer was used to measure the thixotropy at rotation speeds of 10 rpm and 50 rpm. The viscosity at 10 rpm was determined by dividing the viscosity at 50 rpm, and the thixotropy value was calculated. If the value is large, the shape retention is high and it is possible to apply the adhesive thickly. Thixotropy was measured every 2 hours, and if the thixotropy was 3 or more after 8 hours, it was rated as ⊚. Less than 3 Those with a rating of 3 or less were rated as ◯. It is difficult to apply thickly, so the application is limited to thin coating. Furthermore, to confirm whether thick coating is possible, we confirmed whether it is possible to apply a coating of 0.7 mm thickness. Apply with needle 18G (inner diameter 0.84mm), application height of 0.7mm or more is ◎, 0.7m Those less than m were marked as ◯.
[0067] In Example 16, the thixotropy was about 1, and it was not possible to apply the coating to a thickness of 0.7 mm or more. Similarly, in Example 29, the composition of Example 16 was mixed with a high silica filler to give it a high viscosity. However, the thixotropy was about 1, and the thick coating properties were similar to those of Example 16. In addition to inorganic thixotropic agents, organic thixotropic agents were also used for 0-37. The thixotropy was 3 or more, and it was possible to apply a coating thickness of 0.7 mm or more. This is because the inorganic thixotropy The silica surface of the agent has numerous hydroxyl groups, which interact with the functional groups of the organic thixotropic agent. Therefore, it is assumed that the thixotropy was high.
[0068] [Table 6]
[0069] The thixotropic agents and fillers in the table are as follows. RHEOCIN, RHEOBYK-430, RHEOBYK-431, RHEOBYK-R606: BYK product names Disparlon 3600N, 3900EF: Product name manufactured by Kusumoto Chemicals Co., Ltd. FB-5D: Denka product name [Explanation of symbols]
[0070] 1 Inkjet head 2. Recording element board 3 Supply Channel 4 Support member 5 Flow path components 6 First flow path member 7 Second flow path member 8 Third flow path member
Claims
1. Preparation of an epoxy resin composition comprising an epoxy resin, a solid basic compound, and a polythiol A manufacturing method comprising: a step of kneading the epoxy resin and the solid basic compound to produce a mixture 1; and kneading the polythiol into the substance 1 to produce a mixture 2. A method for producing an epoxy resin composition.
2. An epoxy resin composition comprising an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol. A method for producing a composition, comprising the steps of: a step of producing a mixture 3 by kneading the epoxy resin and the thixotropic agent; kneading the solid basic compound with the mixture 3 to produce a mixture 4; kneading the polythiol into the mixture 4 to produce a mixture 5; Epoxy resin composition according to claim 1,
3. An epoxy resin composition comprising an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol. A method for producing a composition, comprising the steps of: a step of kneading the epoxy resin and the solid basic compound to produce a mixture 1; A step of kneading the polythiol and the thixotropic agent to produce a mixture 6; kneading the mixtures 1 and 6 to produce a mixture 7; Epoxy resin composition according to claim 1,
4. An epoxy resin composition comprising an epoxy resin, a thixotropic agent, a solid basic compound, and a polythiol. The method for producing a composition includes the step of producing a mixture 3 by kneading the epoxy resin and the thixotropic agent. a step of kneading the solid basic compound into the mixture 3 to produce a mixture 4; a step of kneading the mixture 4 and the thixotropic agent to produce a mixture 6; and producing product 8.
5. The content of the thixotropic agent is 1 to 20 parts by mass relative to 100 parts by mass of the epoxy resin. The method for producing an epoxy resin composition according to claim 3 or 4, wherein the components are mixed so as to be in a state where the components are mixed in a manner such that the components are in a state where ...
6. 6. Any one of claims 1 to 5, wherein the polythiol is a polythiol having an ether skeleton.
2. A method for producing the epoxy resin composition according to claim 1.
7. The thiol equivalent of the polythiol was 0. The method for producing an epoxy resin composition according to any one of claims 1 to 6, wherein the equivalent is 5 to 1.
8. The method according to any one of claims 1 to 7, further comprising the step of adding a silane coupling agent. A method for producing an epoxy resin composition according to claim 1.
9. The silane coupling agent is a silane having an epoxy group and / or a mercapto group. The method for producing an epoxy resin composition according to claim 8, which is a coupling agent.
10. The thixotropic agent is inorganic silica or inorganic silica and an organic thixotropic agent. Item 10. A method for producing an epoxy resin composition according to item 9.
11. The content of the solid basic compound is 3 to 10 parts by mass relative to 100 parts by mass of the epoxy resin. The epoxy resin composition according to any one of claims 1 to 10, Manufacturing method.
12. The epoxy resin includes at least an epoxy resin, a solid basic compound, and a polythiol, The content of the solid basic compound is 3 to 10 parts by mass per 100 parts by mass of the resin. The epoxy resin composition is an epoxy resin composition in which the solid basic compound is encapsulated in the epoxy resin. xy resin composition.
13. The epoxy resin composition according to claim 12, further comprising a thixotropic agent.
14. a recording element substrate for ejecting ink; a recording element substrate for supporting the recording element substrate; a support member having a supply flow path for supplying ink, and a flow path member for supplying ink to the supply flow path A liquid ejection head having The cured product of the epoxy resin composition according to claim 12 or 13 is applied to the recording element substrate and the front surface of the recording element substrate. At least one joint surface between any two of the support member and the flow path member is provided. A liquid ejection head.
15. a recording element substrate for ejecting ink; a recording element substrate for supporting the recording element substrate; a support member having a supply flow path for supplying ink, and a flow path member for supplying ink to the supply flow path A method for manufacturing a liquid ejection head comprising the steps of: An adhesive is produced by the method for producing an epoxy resin composition according to any one of claims 1 to 11. A manufacturing process; At least two of the recording element substrate, the support member, and the flow path member applying the adhesive to one of the joining surfaces to bond the two members together; A method for manufacturing a liquid ejection head comprising the steps of:
16. A first heat curing step for temporarily fixing the two members using the adhesive, and a second heat curing step for temporarily fixing the two members using the adhesive.
16. The liquid ejection head according to claim 15, wherein the second heat curing, which is a main curing that takes a longer time than the first heat curing, is performed in two steps. A method for manufacturing a bed.
Citation Information
Patent Citations
Epoxy resin composition
JP1994211969A
Epoxy resin composition and prepreg
JP1995076647A
Electroconductive resin composition
JP2000230112A
Photo and heat curable composition, and cured product using the same
JP2009051954A
Epoxy resin composition for encapsulation material and encapsulation material
JP2017095571A